2016
DOI: 10.1021/acs.cgd.6b00570
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Transformations of a Crystalline Sponge: Elucidating the Stability of a Highly Porous Three-Dimensional Metal–Organic Framework

Abstract: We present our investigations on the stability of a cobalt thiocyanate-based metal-organic framework (MOF), coordinated by the 2,4,6-tris(4-pyridyl)-1,3,5-triazine (TPT) ligand, which is commonly employed for single-crystal-to-single-crystal guest inclusion. The selected crystalline solid, {[(Co(NCS) 2 ) 3 (TPT) 4 ]·x(solvent)} n , is one emerging MOF currently being utilized as a host for the crystalline sponge method. Our experimental results shed light on two critical structural transformations that should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…21 The nal step at 450 C corresponds to the decomposition of the SCN À ligands. 19 Both i-CoSP and a-CoSP showed mass loss as the samples were heated to 150 C; however, the inactivated sample underwent a larger percent change, consistent with the loss of a greater amount of solvent molecules relative to the activated cage, in which many solvents had already been removed. As the temperature exceeded $160 C, a steep drop in % weight was observed attributed to a loss of o-C 6 H 4 Cl 2 .…”
Section: Thermogravimetric Analysismentioning
confidence: 87%
See 2 more Smart Citations
“…21 The nal step at 450 C corresponds to the decomposition of the SCN À ligands. 19 Both i-CoSP and a-CoSP showed mass loss as the samples were heated to 150 C; however, the inactivated sample underwent a larger percent change, consistent with the loss of a greater amount of solvent molecules relative to the activated cage, in which many solvents had already been removed. As the temperature exceeded $160 C, a steep drop in % weight was observed attributed to a loss of o-C 6 H 4 Cl 2 .…”
Section: Thermogravimetric Analysismentioning
confidence: 87%
“…Murugesu and co-workers recently reported microcrystals of CoSP belonging to the trigonal space group R3m with the same overall structure as the framework reported by Fujita and co-workers, with different solvents of crystallization. 19 It was observed that the orange crystals (i-CoSP; inactive form) transformed to a green semi-amorphous material (a-CoSP; activated form) upon removal from the mother liquor, attributed to the removal of solvent and loss of crystallinity of the framework. In this activated form, guest molecules can occupy the void spaces that once housed solvents of crystallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently a publication about the hidden transformations of the [(ZnI2)3(tpt)2x(solvent)] n crystalline sponge system has been published. 69 The initial difficulty to reproduce the soaking experiments led both Fujita and others to improve the protocols how the sponge crystals should be grown and selected, optimizing the soaking conditions and solvents used, and giving Figure 6. The Hirshfeld 24 surface plot (top) of the C70 guest in the cavity of the dimeric capsule.…”
mentioning
confidence: 99%
“…Solvent molecules are excluded for clarity. Please do not adjust margins Please do not adjust margins guidelines about the actual data collection strategies with an in-house instrument 67,[69][70][71][72][73] or synchrotron radiation.…”
mentioning
confidence: 99%